The Lifestyle Medicine Outpatient Clinic at Loma Linda University Health. Issue 5 (September 2018) - Cramer, Tonya; Rea, Brenda
Medical management of chronic health concerns relies heavily on behavioral change, most specifically medication adherence. Yet approximately 50% of patients with chronic illnesses are not thought to take their medications as prescribed. Moreover, it is recognized that lifestyle and behavioral changes can reduce the need for medication. It is well documented that patient outcomes and their success in achieving behavioral change is improved with engagement and support from a medical care team. As the inpatient lifestyle medicine service was being conceptualized at Loma Linda University Health (LLUH), it became apparent that an outpatient service would be necessary for follow-up care of the patients and support the lifestyle medicine treatments initiated in the hospital. Additionally, an outpatient clinic would be available to the patient population at Loma Linda and potentially prevent hospitalizations, morbidity, and mortality with proactive lifestyle medicine treatment. The initial outpatient clinic opened in February 2017 and was soon expanded to meet patient demand. Currently, the LLUH Lifestyle Medicine Outpatient Clinic is available 5 days a week, utilizing 5 physicians.